Ten new species of Phyllagathis (Trib. Sonerileae, Melastomataceae ) from Sarawak, Borneo - Lin, Che-Wei; Chen, Chien-Fan; Yang, T.y. Aleck (Phytotaxa, 2017)
Ten undescribed species of Phyllagathis from southwestern Sarawak, named P. bicolor, P. lii, P. millelunata, P. phyllioides, P. rivularis, P. rubrosetosa, P. ulu, P. violinifolia, P. wallacei and P. yodae are reported in this study. We describe and illustrate the ten new species after a careful study of the literature, herbarium specimens and living plants.